2022
DOI: 10.3389/fped.2022.894846
|View full text |Cite
|
Sign up to set email alerts
|

Standard and increased canakinumab dosing to quiet macrophage activation syndrome in children with systemic juvenile idiopathic arthritis

Abstract: ObjectiveMacrophage activation syndrome (MAS) is a life-threatening, potentially fatal condition associated with systemic juvenile idiopathic arthritis (sJIA). Interleukin-1 (IL-1) is a key cytokine in the pathogenesis of sJIA MAS. Many cases of MAS are medically refractory to traditional doses of biologic cytokine inhibitors and may require increased dosing. When MAS occurs in the setting of sJIA treated with the IL-1 receptor antagonist (IL-1Ra), anakinra, increased anakinra dosing may be beneficial. Increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Patient 1 received a dose of 8 mg/kg for the first time due to uncontrolled MAS, showing minimal response to the treatments in methylprednisolone pulse, etoposide, and doxorubicin liposome. Kostik MM et al described that 50% of patients received one scheduled injection of an increased dose (2–3 times standard doses) of canakinumab with rapid resolution of sJIA-associated MAS allowing for tapering back down to standard canakinumab dosing of 4 mg/kg every 4 weeks ( 15 ). In addition, 45.5% of patients in our study were given to JAKi at the initiation of canakinumab treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Patient 1 received a dose of 8 mg/kg for the first time due to uncontrolled MAS, showing minimal response to the treatments in methylprednisolone pulse, etoposide, and doxorubicin liposome. Kostik MM et al described that 50% of patients received one scheduled injection of an increased dose (2–3 times standard doses) of canakinumab with rapid resolution of sJIA-associated MAS allowing for tapering back down to standard canakinumab dosing of 4 mg/kg every 4 weeks ( 15 ). In addition, 45.5% of patients in our study were given to JAKi at the initiation of canakinumab treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers reasonably expect that the frequency of MAS in sJIA can be potentially reduced through treatment with IL-1 blockades [ 11 ]. Kostik et al [ 32 ] reported on eight patients with sJIA who developed MAS that was resolved by a short-term increase in canakinumab doses in all patients. In our study, three patients experienced four MAS events in the past, however, none developed MAS during canakinumab treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several patients had the dose of canakinumab increased and they experienced the resolution of MAS. And there were no notable short-term adverse events (160). In a case-based review of Deniz Gezgin Yıldırım et al, a case that did not respond to anakinra but well responded to canakinumab was reported (161).…”
Section: Il-1mentioning
confidence: 99%